Systemic Immune Activation Profiles of HIV-1 Subtype C-Infected Children and Their Mothers - Tinyiko G. Makhubele; Helen C. Steel; Ronald Anderson; Gisela van Dyk; Annette J. Theron; Theresa M. Rossouw (Hindawi Limited, 2016)
Little is known about immune activation profiles of children infected with HIV-1 subtype C. The current study compared levels of selected circulating biomarkers of immune activation in HIV-1 subtype C-infected untreated mothers and their children with those of healthy controls. Multiplex bead array, ELISA, and immunonephelometric procedures were used to measure soluble CD14 (sCD14), beta-2 microglobulin (β2M), CRP, MIG, IP-10, and transforming growth factor beta 1 (TGF-β1). Levels of all 6 biomarkers were significantly elevated in the HIV-infected mothers and, with the exception of MIG, in their children (P<0.01-P<0.0001). The effects of antiretroviral therapy (ART) and maternal smoking on these biomarkers were also assessed. With the exception of TGF-β1, which was unchanged in the children 12 months after therapy, initiation of ART was accompanied by decreases in the other biomarkers. Regression analysis revealed that although most biomarkers were apparently unaffected by smoking, exposure of children to maternal smoking was associated with a significant increase in IP-10. These findings demonstrate that biomarkers of immune activation are elevated in HIV-infected children pre-ART and decline, with the exception of TGF-β1, after therapy. Although preliminary, elevation of IP-10 in smoke-exposed infants is consistent with a higher level of immune activation in this group.